Aquaporin‐9 is expressed in rat Sertoli cells and interacts with the cystic fibrosis transmembrane conductance regulator. Issue 9 (1st October 2014) - Jesus, Tito T.; Bernardino, Raquel L.; Martins, Ana D.; Sá, Rosália; Sousa, Mário; Alves, Marco G.; Oliveira, Pedro F.
Abstract Men with mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene are usually subfertile/infertile. Besides playing a role in Cl−/HCO3− transport, it has been proposed that CFTR interacts with water membrane transport systems, particularly aquaporins, to control seminiferous tubular secretion, which is regulated by the somatic Sertoli cells (SCs). As aquaporin‐9 (AQP9) is highly expressed throughout the male reproductive tract, we hypothesized that it is also present in rat SCs and that it physically interacts with CFTR. To test this hypothesis, primary cultures of rat SCs were established, and expression of CFTR and AQP9 was assessed by RT‐polymerase chain reactions (mRNA) and Western blot analysis (protein). A coimmunoprecipitation assay was used to evaluate the physical interaction between CFTR and AQP9. Our results show that CFTR and AQP9 are expressed in rat SCs. We were also able to detect a molecular interaction between CFTR and AQP9 in rat SCs. This is the first report describing the presence of AQP9, and its interaction with CFTR, in rat SCs. Moreover, our results provide evidence that CFTR is involved in water homeostasis of the seminiferous tubular secretion. These mechanisms may open new insights on therapeutic targets to counteract subfertility/infertility in men with cystic fibrosis and mutations in the CFTR gene. © 2014 IUBMB Life, 66(9):639–644, 2014